Vitamin D serum levels are associated with handgrip strength but not with muscle mass or length of hospital stay after hip fracture - Gumieiro, David Nicoletti [UNESP]; Murino Rafacho, Bruna Paola [UNESP]; Buzati Pereira, Bruna Leticia [UNESP]; Cavallari, Rarelin Alvisi [UNESP]; Tanni, Suzana Erico [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Mamede Zornoff, Leonardo Antonio [UNESP]; Dinhane, Daniel Innocenti [UNESP]; Innocenti Dinhane, Kandir Genesio [UNESP]; Cacao Pereira, Gilberto Jose [UNESP]; Rupp de Paiva, Sergio Alberto [UNESP]; et al. (Elsevier B.V., 2015)
Objectives: The aim of this study was to evaluate the association between serum levels of 25(OH) vitamin D-3 with midupper arm muscle circumference (MUAMC), handgrip strength and length of hospital stay (LOS) after hip fracture.Methods: In total, 102 consecutive patients with hip fracture over the age of 65 were admitted to the orthopedic unit and prospectively evaluated. All of the patients were treated according to specific protocols depending on the type of fracture. Anthropometric measurements and handgrip strength were performed, and blood samples were taken for serum biochemistry and 25(OH) vitamin D-3 analysis within the first 72 h of admission. All of the patients were followed during their hospital stay, and the length of stay was recorded.Results: Of the patients, two were excluded because of pathologic fractures. In total, 100 patients with a mean age of 80 +/- 7 y were included in the analysis. Among these patients, 73% were female, and 37% had vitamin D deficiency. The median LOS was 7 (5-11) d. Patients with vitamin D deficiency had lower handgrip strength in univariate analysis. In the multiple linear regression analysis with robust standard error, serum vitamin D levels adjusted by age and sex were associated with handgrip strength but not with MUAMC and LOS after hip fracture.Conclusions: In conclusion, vitamin D serum levels were associated with handgrip strength but not with muscle mass or length of hospital stay after hip fracture. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Vitamin D; Sarcopenia; Dynapenia; Hip fracture